Emotion Regulation and its Influence on Body-Related Distress in Overweight Women. Issue 5 (December 2013) - Svaldi, Jennifer; Naumann, Eva; Trentowska, Monika; Lackner, Helmut K.; Tuschen-Caffier, Brunna
Overweight and obese individuals are at greater risk for the development of a major depressive disorder. A main factor contributing to negative affect in obese women is body-related worrying. Given the potential benefits of various emotion regulation (ER) strategies in the modification of negative affect, the aim of the present study was to test whether experimentally-induced body dissatisfaction can be modified by ER strategies in obese women. Body dissatisfaction was experimentally induced in a group of 37 obese women using model pictures. Following this, participants were randomly assigned to two different ER strategies: rumination on present emotions and thoughts, or acceptance of whatever thoughts and feelings come up. Weight and appearance satisfaction, distress about body feelings and mood were assessed both prior to, immediately after, and 4 min after the induction. Psychophysiological parameters were assessed continuously. The main results reveal that after the use of ER strategies, weight and appearance satisfaction returned to baseline levels. However, in the rumination condition, distress about body feelings remained above and mood below baseline. In the acceptance condition distress and mood returned to baseline levels. The results are discussed in terms of the usefulness of ER strategies with regard to reducing body-related distress.